Equilibrium Point Bifurcation and Singularity Analysis of HH Model with Constraint - Xinhe Zhu; Zhiqiang Wu (Abstract and Applied Analysis)
We present the equilibrium point bifurcation and singularity analysis of HH model with constraints. We investigate the effect of constraints and parameters on the type of equilibrium point bifurcation. HH model with constraints has more transition sets. The Matcont toolbox software environment was used for analysis of the bifurcation points in conjunction with Matlab. We also illustrate the stability of the equilibrium points.